Effect of arm position on the aerodynamic drag of an individual time trial position - Maddocks, P.; Walker, A. D. (Sports Engineering, 2025)
In an individual time trial elite cyclists strive to reduce aerodynamic drag through the optimisation of body position. This paper presents an aerodynamic investigation into the effect of arm position on drag using Computational Fluid Dynamics. The lowest drag was achieved by moving the hands/arms into a higher position in conjunction to narrowing the elbows better guided the air over the rider`s head and away from the centre of the rider`s body. This gave a reduction in drag area of 11.2% which would translate to a time saving of about 91 s for a 40 km time trial ridden at 14 m/s (50.4 km/h). For all positions about half the drag generated by the rider was produced by the legs. A lower hand position was observed to reduce the drag from the legs but with no net gain as drag from the head, arms and body increased. For the positions tested a reduction in projected frontal area did not automatically reduce aerodynamic drag. A more complex relationship between area and aerodynamic drag coefficient existed. However, the results show clear potential for (i) better aerodynamic integration of the arms with the legs or (ii) raising the rider`s head into a safe forward-looking position without compromising the aerodynamic drag.